Berberine suppresses influenza virus‐triggered NLRP3 inflammasome activation in macrophages by inducing mitophagy and decreasing mitochondrial ROS. Issue 1 (9th April 2020) - Liu, Hui; You, Leiming; Wu, Jun; Zhao, Mengfan; Guo, Rui; Zhang, Haili; Su, Rina; Mao, Qin; Deng, Di; Hao, Yu
Abstract: Berberine (BBR) is an isoquinoline alkaloid extracted from several commonly used Chinese herbs. Our previous studies demonstrated BBR‐mediated alleviation of lung injury due to inflammation and decrease in the mortality of mice with influenza viral pneumonia. The recent argument of autophagy against inflammatory responses has aroused wide concerns. This study focuses on the reactive oxygen species‐Nod‐like receptor protein 3 (ROS‐NLRP3) pathway to investigate whether BBR inhibits NLRP3 inflammasome activation by inducing mitophagy. Our results demonstrate that BBR and mitochondrion‐targeted superoxide dismutase mimetic (Mito‐TEMPO; a specific mitochondrial ROS scavenger) significantly restricted NLRP3 inflammasome activation, increased mitochondrial membrane potential (MMP), and decreased mitochondrial ROS (mtROS) generation in J774A.1 macrophages infected with PR8 influenza virus. These observations suggest that the inhibitory effects of BBR on NLRP3 inflammasome activation were associated with the amelioration of mtROS generation. BBR treatment induced regular mitophagy, as evident from the increase in microtubule‐associated protein 1 light chain 3 II, decrease in p62, colocalization of LC3 and mitochondria, and formation of autophagosomes. However, 3‐methyladenine, an autophagy inhibitor, reversed the inhibitory effects of BBR on mitochondrial damage and NLRP3 inflammasome activation in influenza virus‐infected macrophages, indicating the involvement of mitophagy in mediating the inhibitory effects of BBR on NLRP3 inflammasome activation. Furthermore, the knockdown of Bcl‐2/adenovirus E18‐19‐kDa interacting protein 3 (BNIP3) expression attenuated the effects of BBR on mitophagy induction to some extent, suggesting that the BBR‐induced mitophagy may be, at least in part, mediated in a BNIP3‐dependent manner. Similar results were obtained in vivo using a mouse model of influenza viral pneumonia that was administered with BBR. Taken together, these findings suggest that restricting NLRP3 inflammasome activation by decreasing ROS generation through mitophagy induction may be crucial for the BBR‐mediated alleviation of influenza virus‐induced inflammatory lesions. Abstract : Berberine inhibited influenza virus‐induced excessive inflammatory responses, restricting NLRP3 inflammasome activation by decreasing ROS generation and inducing mitophagy.